Modeling University Business Incubator For SMEs Digitalisation - Huda, Nisrina Nafi'atul; Rejito, Cattleya (Program Studi Sistem Informasi Universitas Atma Jaya Yogyakarta, 2020)
The emergence of changes in various aspects of human life due to the global pandemic COVID-19 not only affects large or multi-national companies, but it also has several impacts on SMEs. Over the numerous barriers and unreadiness of SMEs in facing technological developments, they are forced by circumstances to immediately adapt and digitize their business processes. Universities, through its richness of research and resources are believed to be appropriate agent to help SMEs overcome this completely new situation. Universities are expected to be able to generate innovations, providing such opportunities to SMEs to build their competitive advantage to keep sustain in this uncomfortable condition. One option that can be done is to incubate the SMEs in the university business incubator. However, to date, research that related to university business incubators specializing in managing SMEs is still very limited. Current research on business incubators is dominated by studies of business incubators related to start-ups and new technology-based firm . Therefore, this research was conducted to develop a conceptual model of university business incubator with the main objective of helping the SMEs to digitize the business they run. This research was conducted using the literature study method and obtained a university business incubator model consisting of four components or stages, namely preparation, pre-incubation, incubation, and post-incubation.